Intake and ingestive behavior of rams fed with increasing inclusions of babassu endocarp meal I in their diet (Orbignya spp.) - Sá,Hemilly Cristina Menezes de (2014)
The objective of this work was to investigate the ingestive behavior of sheep fed with different inclusions of babassu endocarp meal I. The animals receive isofibrous, isoenergetic and isonitrogenous diets containing the by-product in increasing levels of inclusion (zero; 7,5%; 15%; 22,5%). Twenty rams were used in this study and distributed in four treatments with five repetitions each. The ingestive behavior was conducted over a period of 24 hours, with visual observations at 5 minutes intervals and the variables being: idle, ruminating, feeding and chewing. The study demonstrated that the dry matter intake in function of the body weight and the metabolic weight decreased linearly as the babassu endocarp meal I was included in the diet. The feeding, ruminating and chewing efficiency when expressed in grams/dry matter/hour was reduced in a linear response with the different inclusions of the by-product. The ingestive behavior of feeding, idle, rumination and chewing activities in minutes/day was not altered in this study